PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS MURID KELAS V SD INPRES SARUDU V KABUPATEN PASANGKAYU PROVINSI SULAWESI BARAT - Radawiah Iskandar; Muhammad Nawir; Hidayah Quraisy (Jurnal Riset Guru Indonesia, 2023)
The research carried out was class action research (CAR). This research was conducted in two cycles which included four meetings. Data collection techniques are observation, test (evaluation), and documentation. The data obtained were then analyzed using quantitative and qualitative descriptive analysis. The results of the study showed an increase in social studies learning outcomes for fifth-grade students at SD Inpres Sarudu V, Pasangkayu Regency. Likewise, the observed data in each cycle showed a positive change in student attitudes. The above can be seen from the increase in student learning outcomes, namely the class average score in the pre-cycle was 72 then in the first cycle it became 72 and in the second cycle it became 77. The number of students who were able to achieve KKM ≥ 70 in the pre-cycle there were 11 students, in the second cycle I have 14 students, and in cycle II there are 21 students. The percentage of completeness in the pre-cycle was 52%, the first cycle was 66% and the second cycle was 100%, so that in the second cycle, more than 80% of students achieved the KKM criteria ≥70.